(untitled) (Kairaranga, 2008)
This paper discusses the complexities of engaging with Pasifika communities in Aotearoa New Zealand and examines the assumption that the best people to provide services to Pasifika children have to be Pasifika. The paper offers strategies on building the capability of non-Pasifika staff to work with Pasifika children and their families.